THE IMPACT OF COVID-19 PANDEMIC ON THE INCOME OF MICRO SMALL MEDIUM ENTERPRISES IN SELLING EEL CHIPS AT GODEAN DISTRICT - Dewi, Marina Kusuma; Bintariningtyas, Selfia (Journal of Applied Economics in Developing Countries, 2021)
The aim of this study was to explain the difference between the income before and after the Covid-19 pandemic for the selling of eel chips by the micro small medium enterprises (MSME) in Godean district. The method of the study is quantitative with the Wilcoxon test. The sample on this study were 38 sellers. The data collection was done by using a questionnaire via google form or was done directly to the target sellers. The results of the study based on the Wilcoxon test showed that there was a significant difference between the income before and after the Covid-19 pandemic on the eel chips sellers in Godean district that has decreased the sales during the Covid-19 pandemic. Keywords: Income, Covid-19, Pandemic, Eel chips, Godean